In Pursuit of Leviathan : Technology, Institutions, Productivity, and Profits in American Whaling, 1816-1906. - Davis, Lance E. (Lance Edwin) (National Bureau of Economic Research Series on Long-Term Factors in Economic Development., 1997)
In Pursuit of Leviathan traces the American whaling industry from its rise in the 1840s to its precipitous fall at the end of the nineteenth century. Using detailed and comprehensive data that describe more than four thousand whaling voyages from New Bedford, Massachusetts, the leading nineteenth-century whaling port, the authors explore the market for whale products, crew quality and labor contracts, and whale biology and distribution, and assess the productivity of the American fleet. They then examine new whaling techniques developed at the end of the nineteenth century, such as modified cl.